Pengaruh Stres Kerja Dan Komitmen Organisasi Terhadap Kepuasan Kerja Berdasarkan Gender Pada Warong Miyabi Bali - Putra, I Gede Suwardiana; Wibawa, I Made Artha (E-Jurnal Manajemen, 2014)
This study aimed to examine the effect of work stress and organizational commitment on job satisfaction by gender. Respondents were 35 employees was determined using saturated or census sampling method, where respondents were permanent employees other than the manager and his deputy. Data were obtained by questionnaires were analyzed using discriminant analysis techniques (discriminant analysis). Based on the results of the analysis found that work stress and organizational commitment simultaneously significant effect on job satisfaction. Work stress was partially significant effect on job satisfaction. Organizational commitment was partially significant effect on employee job satisfaction. Keywords : Gender , Work Stress, Organizational Commitment, and Job Satisfaction
Keywords: Gender, Work Stress, Organizational Commitment, and Job Satisfaction